Synchronous Counter Design Using Novel Level Sensitive T-FF in QCA Technology - Majeed, Ali H.; Alkaldy, Esam; bin Zainal, Mohd Shamian; Bin MD Nor, Danial (Journal of low power electronics and applications, 2019)
The quantum-dot cellular automata (QCA) nano-technique has attracted computer scientists due to its noticeable features such as low power consumption and small size. Many papers have been published in the literature about the utilization of this technology for de-signing many QCA circuits and for presenting logic gates in an optimal structure. The T flip-flop, which is an essential part of digital designs, can be used to design synchronous and asynchronous counters. This paper presents a novel T flip-flop structure in an optimal form. The presented novel gate was used to design an N-bit binary synchronous counter. The QCADesigner software was used to verify the designed circuits and to present the simulation results, while the QCAPro tool was used for the power analysis. The proposed design required minimal power and showed good improvements over previous designs.